Pengaruh Jenis Merger Dan Akuisisi Terhadap Kinerja Keuangan Perusahaan Go Public Yang Terdaftar Di Bursa Efek Indonesia - Miftahul Jannah (CV. Syntax Corporation Indonesia, 2020)
The purpose of this study is to determine the effect of mergers and acquisitions on financial performance and determine the effect of types of mergers and acquisitions on financial performance. Financial performance is measured by financial ratios consisting of Return On Asset, Current Ratio, Total Asset Turnover and Debt to Equity Ratio. The sample in this study is 42 companies that conducted mergers and acquisitions in 2012-2017. This study use one sample t test to test the effect of mergers and acquisitions on financial performance and uses regression linear with dummy variables to test the effect of types mergers and acquisitions on financial performance. The results of this study show mixed results, ROA and TATO shows a significant decrease after merger and acquisitions, DER shows a significant increase and CR shows an insignificant decrease. While for the types of mergers and acquisitions, no effect was found on financial performance.